2021
DOI: 10.3390/foods10040842
|View full text |Cite
|
Sign up to set email alerts
|

Which Company Characteristics Make a Food Business at Risk for Food Fraud?

Abstract: Fraud can happen to any food business, but some sectors show more historical evidence of food fraud than others. This may be due to particular company characteristics that affect a company’s level of vulnerability. In the current study, we examined the relevance of the industry segment, business size, and location of food businesses on their food fraud vulnerabilities. Over 8000 food fraud vulnerability self-assessments conducted by food businesses active in 20 industry segments located in five continents were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Specifically, Belgian quality managers employed in plant-based food companies estimated their food integrity climate higher than their counterparts in animal-based food companies. Since plant-derived or plant-based products tend to have, in general, a lower vulnerability to food fraud as compared to animal-derived or animal-based products (Van Ruth & Nillesen, 2021), it is plausible that quality managers of plant-based food companies perceive food integrity higher, as they feel lower risks having to deal with less food safety hazards or food fraud threats than animal-based food companies. Also in the study of Jacxsens et al (2015) it was demonstrated that animal-based food products are on a higher risk level in terms of probability of contamination, since they have intrinsically higher prevalence of pathogens and are often implicated in foodborne outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Belgian quality managers employed in plant-based food companies estimated their food integrity climate higher than their counterparts in animal-based food companies. Since plant-derived or plant-based products tend to have, in general, a lower vulnerability to food fraud as compared to animal-derived or animal-based products (Van Ruth & Nillesen, 2021), it is plausible that quality managers of plant-based food companies perceive food integrity higher, as they feel lower risks having to deal with less food safety hazards or food fraud threats than animal-based food companies. Also in the study of Jacxsens et al (2015) it was demonstrated that animal-based food products are on a higher risk level in terms of probability of contamination, since they have intrinsically higher prevalence of pathogens and are often implicated in foodborne outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have used intelligence derived from on-line media sources [84,85] to provide insight into existing phenomenon informing causal investigation [65]. The five cases highlight common and differentiated case characteristics and how these characteristics frame the incidents, and the wider positioning of how organic food fraud may occur [75].…”
Section: Methodsmentioning
confidence: 99%
“…Fraudulent products are produced to lower standards with a lower cost structure [15]. Food fraud scandals may even result in substantial damage to the reputation of the entire organic food industry [75]. Thirdly such poor practices undermine confidence in food products certified as being organic ultimately eroding trust and reducing the value associated with the credence characteristics of the product [15].…”
Section: Economic Drivers Cultural and Behavioral Driversmentioning
confidence: 99%
“…The effect of industry segment on fraud vulnerability appears fairly similar across continents, whereas the effect of business size exhibits large geographical variation. The results demonstrate that those involved in animal product supply chains and end of chain nodes (catering & retail) feel most vulnerable, and so are larger businesses, and businesses located in Africa and Asia (van Ruth & Nillesen, 2021).…”
Section: Towards a Food Fraud Vulnerability Assessment Toolmentioning
confidence: 96%